حضرت زینب ؑ کی شخصیت اور بحرانی حالات میں نظامت: Personality of Hazrat Zainab and Management in the situations of Crisis (Al-Qamar, 2022)
One of the many difficulties in Islamic society is that they do not take examples from the ideal personalities of Islam. In this article the researcher has tried that with the help of scientific resources, research should be done on the greatness and sense of governance of Hazrat Zainab in Karbala, because research on the practical nature of the ideal person of Islam can prove to be a symbol of choice. An austere study of historical events in Karbala and Syria confirms the greatness of Hazrat Zainab. It was her genus and wisdom that she everted the victory of Yazid. Being the leader of an unarmed group of defeated people, she applied such shrewd political tactics that completely changed the post-war scenario. Her approach and way of handling the situation could be added as a complete theory to the subject of Political Science.  Therefore, at the beginning of this research, the main problems have been given to the definition of crisis, the purpose of governance, the systematic situation, and the life of Hazrat Zainab ·Then Hazrat Zainab's role in dissolving the crisis of Karbala and the ideal governance has been considered as the imagination of a genus of high rank.
Keywords: Personalities; Governance; Nature; Austere; Systematic